Influence of public and private supports on the organizational culture of green businesses in the Central Special Administrative and Planning Region - Céspedes Gil, Alirio; Díaz Ariza, Diana Marcela; Aguilar Galeano, Estíbaliz; Figueroa Espinel, Julian Francisco (Cooperativismo & Desarrollo, 2021)
This article begins with a theoretical exploration of the concept of organizational culture, relating elements such as business efficiency, adaptability and sustainability, in order to focus the reader on the concepts of organizational performance and thus determine the organizational aspects that would be affected by govern-ment support. The construction of the document focuses on achieving the objective: To determine the effect of governmental and private support on the organizational model of green businesses in the Bogota Region, from a Resource-Based View of the Firm (RBV). For this reason, after the theoretical review phase and the concep-tual framework that guides the reader and supports the categories of analysis, a Multiple Correlation Analysis is applied to sixty-six green businesses in the Central Administrative and Special Planning Region (RAPE in Spanish), by which factorial variables are established which show the relationship between institutions that received support and those that did not, along with the differences that are manifested in their organizational models from the perspective of the RBV
Keywords: green businesses; multiple correlational analysis; organizational model; public support; special central planning